2011
DOI: 10.1093/deafed/enr001
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation of Children and Adolescents With Cochlear Implants: A Qualitative Analysis of Parent, Teacher, and Child Interviews

Abstract: Psychosocial factors, including socioemotional well-being, peer relationships, and social inclusion with hearing and deaf peers, are increasingly becoming a focus of research investigating children with cochlear implants. The study reported here extends the largely quantitative findings of previous research through a qualitative analysis of interviews with parents, teachers, and pediatric cochlear implant users themselves in three eastern states of Australia. We interviewed 24 parents, 15 teachers, and 11 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 55 publications
5
111
1
4
Order By: Relevance
“…In part, that situation may be a result of the sensitivity of the issue, given a history in which deaf individuals were described as impulsive, egocentric, and lagging in moral development (e.g., Altshuler, Deming, Vollenweider, Rainer, & Tendler, 1976;Chess & Fernandez, 1980;Nass, 1964). Yet the lack of an evidence base with regard to the origins of social maturity among deaf learners means that parents and educators are unable to deal with it in any systematic fashion, with potentially negative implications for peer socialization (Caldarella & Merrell, 1997;Punch & Hyde, 2011), academic achievement (Antia et al, 2002), and later employment (Kelly, Quagliata, DeMartino, & Perotti, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In part, that situation may be a result of the sensitivity of the issue, given a history in which deaf individuals were described as impulsive, egocentric, and lagging in moral development (e.g., Altshuler, Deming, Vollenweider, Rainer, & Tendler, 1976;Chess & Fernandez, 1980;Nass, 1964). Yet the lack of an evidence base with regard to the origins of social maturity among deaf learners means that parents and educators are unable to deal with it in any systematic fashion, with potentially negative implications for peer socialization (Caldarella & Merrell, 1997;Punch & Hyde, 2011), academic achievement (Antia et al, 2002), and later employment (Kelly, Quagliata, DeMartino, & Perotti, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that social maturity was measured via self-report in this study, however, and Antia, Jones, Luckner, Kreimeyer, and Reed (2011) found that deaf children appeared overly confident in self-reports of social competence relative to parent and teacher ratings. Furthermore, deaf individuals with poor social competence, or simply poor communication skills, may be less aware of subtleties in social interactions and the extent of their delays (Most, Ingber, & Heled-Ariam, 2012;Punch & Hyde, 2011).…”
Section: Relations Among Communication Social Maturity and Executivmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there appear to be no negative reports on social/emotional development of children as a result of cochlear implantation, a cochlear implant will not guarantee that the social difficulties experienced by many children with severe-profound hearing loss are avoided (Punch & Hyde, 2011). The research does offer hope, however, that an early cochlear implant may not only facilitate the development of speech and language skills, but can also give children the potential to develop a healthy and positive social identity and competent interactional skills.…”
Section: Social and Emotional Developmentmentioning
confidence: 99%
“…In the United States and other developed nations, the diffusion of such intervention strategies including a surgical procedure has been very rapid and widespread despite the fact that the success rates of these interventions tend to vary greatly depending on many other factors such as parental educational levels with failure rates approaching 20-50% in some studies (Gulya et al, 2010;Peterson et al, 2010;Bouchard et al, 2008). Studies that examine other measurable and meaningful outcomes of these auditory-based interventions for deaf children such as essential language development and long-term quality of life and studies that include alternative strategies to develop deaf children's language through visual modalities such as signed languages Punch & Hyde, 2011) have only very recently begun to penetrate the medical literature that influence hearing professionals and parents in their decision-making regarding the best ways to promote deaf children's and deaf people's long-term outcomes.…”
Section: Interpersonal: the Deaf Person Is Usually A Visual Minority mentioning
confidence: 99%